A preliminary investigation of cranial sexual dimorphism in a Northern Territory population. (29th July 2019) - Swift, Lauren; Flavel, Ambika; Franklin, Daniel
ABSTRACT: In the discipline of forensic anthropology, the concept of population specificity ensures that the most accurate methodologies are applied to a given set of skeletal remains. It has been shown that the use of sex estimation standards derived using a population that is temporally and/or geographically removed from the population of the decedent results in misclassification and an unacceptably large sex bias. The current study explores the latter by applying two established cranial sex estimation standards, Giles and Elliot (1963) and Franklin (2013), to a previously untested population from the Northern Territory, Australia. The results demonstrate a reduction in classification accuracy when applying both standards, with an increase in the sex bias for all discriminant functions tested. These results indicate that utilizing foreign standards to estimate sex within the Northern Territory will likely result in misclassification, thus indicating the need for more accurate standards that reflect the sexual dimorphism in the contemporary Northern Territory population.